Acquisition of prescribing skill by medical students in a problem-based learning curriculum: preclerkship to clerkship phase transition - Al Khaja, Khalid A.J.; James, Henry; Sequeira, Reginald P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Medical school training for students in pharmacotherapy is sub-optimal and junior doctors are not confident to prescribe drugs. This study was conducted to assess the prescribing competency of students in preclerkship and clerkship phases at a medical school that implements problem-based learning curriculum. Methods: Objective structured practical examination was used to assess prescribing competency of students in both phases. The prescribing performance was empirically categorized into poor, moderate and good competency. Results: The prescription writing skills achieved by the clerkship students did not significantly differ from that attained by students in preclerkship phase. Good prescribing competency was attained by approximately 20% of the students at the end of both phases. Preclerkship students performed better on therapeutic reasoning than those in clerkship phase. Cognitive skill that involves choosing the superior drug(s) among several alternatives as achieved less satisfactorily by majority of students from both phases of the program. Conclusions: Acquisition and further development of the prescribing competency during the clerkship phase was sub-optimal. The continuation of pharmacotherapeutic context-learning program during clerkship phase is recommended.